2020
DOI: 10.3390/rs12162568
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical and Sedimentological Investigations Integrate Remote-Sensing Data to Depict Geometry of Fluvial Sedimentary Bodies: An Example from Holocene Point-Bar Deposits of the Venetian Plain (Italy)

Abstract: Over the past few millennia, meandering fluvial channels drained coastal landscapes accumulating sedimentary successions that today are permeable pathways. Propagation of pollutants, agricultural exploitation and sand liquefaction are the main processes of environmental interest affecting these sedimentary bodies. The characterization of these bodies is thus of utmost general interest. In this study, we particularly highlight the contribution of noninvasive (remote and ground-based) investigation techniques, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A similar contrast between the external geometry of meanders and the architecture of related point bars has been highlighted for fluvial meanders (Russell et al ., 2019) through the analysis of their complex scroll‐bar patterns. Fluvial and tidal point bars are assumed to arise from a progressive increase in sinuosity of relatively straight channels (Leopold & Wolman, 1960; Daniel, 1971; Brice, 1974; Lewin, 1976; Nanson & Page, 1983; Knighton & Woodroffe, 1992; Hughes, 2012; Ghinassi et al ., 2014), although the planform patterns of newly‐formed channels are commonly irregular, being controlled by adaptation of the flow to local micro‐reliefs of the newly‐drained areas (Aslan & Blum, 1999; Taylor, 1999; Motta et al ., 2012; Cassiani et al ., 2020; Bellizia et al ., 2021). Although adaptation of the Holocene lagoon mud to the underlying alluvial lowstand topography (Castiglioni & Favero, 1987; Amorosi et al ., 2008) could have generated the micro‐relief required to trigger wandering of a newly‐formed channel, an avulsive relocation (Slingerland & Smith, 1998, 2004; Mohrig et al ., 2000) of the study channel is ruled out by the lack of a significant superelevation between sub‐tidal channels and surrounding overbanks.…”
Section: Discussionmentioning
confidence: 99%
“…A similar contrast between the external geometry of meanders and the architecture of related point bars has been highlighted for fluvial meanders (Russell et al ., 2019) through the analysis of their complex scroll‐bar patterns. Fluvial and tidal point bars are assumed to arise from a progressive increase in sinuosity of relatively straight channels (Leopold & Wolman, 1960; Daniel, 1971; Brice, 1974; Lewin, 1976; Nanson & Page, 1983; Knighton & Woodroffe, 1992; Hughes, 2012; Ghinassi et al ., 2014), although the planform patterns of newly‐formed channels are commonly irregular, being controlled by adaptation of the flow to local micro‐reliefs of the newly‐drained areas (Aslan & Blum, 1999; Taylor, 1999; Motta et al ., 2012; Cassiani et al ., 2020; Bellizia et al ., 2021). Although adaptation of the Holocene lagoon mud to the underlying alluvial lowstand topography (Castiglioni & Favero, 1987; Amorosi et al ., 2008) could have generated the micro‐relief required to trigger wandering of a newly‐formed channel, an avulsive relocation (Slingerland & Smith, 1998, 2004; Mohrig et al ., 2000) of the study channel is ruled out by the lack of a significant superelevation between sub‐tidal channels and surrounding overbanks.…”
Section: Discussionmentioning
confidence: 99%
“…Architectural 3D reconstructions show that landward sides of several point bars (for example, site C) are finer grained and muddier than the seaward sides. This streamwise grain‐size distribution contrasts with that of fluvial point bars, where the upstream side is generally coarser or slightly coarser than the downstream one (Nanson, 1980; Bridge et al ., 1995; Burge & Smith, 2009; Ielpi & Ghinassi, 2014; Yan et al ., 2017; Russell et al ., 2019; Cassiani et al ., 2020). This atypical grain‐size distribution is consistent with accumulation of mud on the landward side of point bars, that represents a sheltered zone during tidal floods.…”
Section: Discussionmentioning
confidence: 99%
“…The choice to compare simulation results based on reconstructed and idealized bar complexes highlights the importance of accurate 3D geometric modeling of the subsurface deposits to properly predict groundwater flows. The use of simplistic models (Brice, 1974;Finotello et al, 2018;Lewin, 1976;Nanson and Page, 1983;Wu et al, 2015) can underestimate the effective permeable volume in the subsoil, as shown by Bellizia et al (2021); Cassiani et al (2020), thus limiting the accuracy of the prediction of the effective propagation styles (see fig. 10).…”
Section: Discussionmentioning
confidence: 99%